2011
DOI: 10.48550/arxiv.1107.3696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Solitons in graphene

Abstract: In this paper we demonstrate the direct evidence of solitons in graphene by means of molecular dynamics simulations and mathematical analysis. It shows various solitons emerge in the graphene flakes with two different chiralities by cooling procedures. They are in-plane longitudinal and transverse solitons. Their propagations and collisions are studied in details. A soliton solution is derived by making several valid simplifications. We hope it shed light on understanding the unusual thermal properties of grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Recently, optical solitons have also been investigated in graphene both experimentally and theoretically [46][47][48][49]. The direct evidence of solitons in graphene by means of molecular dynamics simulations and mathematical analysis has been demonstrated [50]. It has been reported that graphene exhibits an extremely strong nonlinear optical response in the THz or infrared regime [51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, optical solitons have also been investigated in graphene both experimentally and theoretically [46][47][48][49]. The direct evidence of solitons in graphene by means of molecular dynamics simulations and mathematical analysis has been demonstrated [50]. It has been reported that graphene exhibits an extremely strong nonlinear optical response in the THz or infrared regime [51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…In the dressed-state picture, this case corresponds to the profound interference situation because the eigenvalues of two of the dressed states intersect. [56] For further discussion about the role of elliptical parameter θ on linear absorption and Kerr nonlinearity of the medium, we display the features of linear absorption and Kerr nonlinearity of medium versus θ in Fig. 4.…”
Section: Resultsmentioning
confidence: 99%
“…. The electron concentration can be estimated to be × N 5 10 12 cm −2 and the substrate dielectric constant turns out to be ε 4.5 r [48][49][50]. These parameter values introduced in the experiment [31,33,34,45,46] rely on the sample quality and the substrate.…”
Section: The Theoretical Model and Basic Equationsmentioning
confidence: 99%